TYPES, FORMS, TIME NORMS OF PRODUCTION IN MECHANICAL ENGINEERING AND THEIR CHARACTERISTICS (European Science Methodical Journal, 2026)
This article provides a comprehensive analysis of the main types, organizational forms, and time norms of production in the mechanical engineering industry. The specific features, technical-economic indicators, and areas of application of single, serial, and mass production types are studied. The importance of time norms in increasing labor productivity at mechanical engineering enterprises and the methodology for calculating them are also described. Recommendations for the development of the mechanical engineering industry in Uzbekistan are provided.